Association Between CST3 Gene Polymorphisms and Large-Artery Atherosclerotic Stroke - Ding, Yarong; Xu, Zhe; Pan, Yuesong; Meng, Xia; Xiang, Xianglong; Li, Hao; Liu, Liping; Wang, Yongjun (Frontiers in Neurology, 2021)
Objective: Cystatin C, a marker of atherosclerosis, is encoded by CST3. We aimed to evaluate whether two Single Nucleotide Polymorphisms (SNPs) of CST3 are correlated with Large artery atherosclerotic stroke (LAAS) and prognosis. Methods: This subgroup analysis of CNSR-III (Third China National Stroke Registry) enrolled acute ischemic stroke (AIS) patients within 7 days from August 2015 to March 2018 in China. rs13038305 and rs911119 of CST3 were selected based on the strong association with Cystatin C concentration. Results: Two loci of CST3 (rs13038305 and rs911119) were analyzed in 3833 ischemic stroke patients. Carriers of T allele in rs13038305 and C allele in rs911119 tend to have lower serum Cystatin C levels (p<0.05). Compared with C/C as a reference in rs13038305, odds ratio (OR) of T/T was 0.486, 95% CI 0.237-0.994, p=0.048. Per C allele of rs13038305 also showed an increased level of low-density lipoprotein cholesterol (LDL-C), β(95% CI) was 1.335(1.008-1.250), p=0.044. No correlation was found between the selected SNPs polymorphisms and stroke prognosis (functional outcome, recurrence and mortality). Conclusions: Carriers of the T allele in rs13038305 tend to have a lower proportion of LAAS. rs13038305 and rs911119 polymorphisms were likely to affect Cystatin C concentration independently of kidney function.